2012
DOI: 10.1186/1472-6750-12-61
|View full text |Cite
|
Sign up to set email alerts
|

Functional enhancement of neuronal cell behaviors and differentiation by elastin-mimetic recombinant protein presenting Arg-Gly-Asp peptides

Abstract: BackgroundIntegrin-mediated interaction of neuronal cells with extracellular matrix (ECM) is important for the control of cell adhesion, morphology, motility, and differentiation in both in vitro and in vivo systems. Arg-Gly-Asp (RGD) sequence is one of the most potent integrin-binding ligand found in many native ECM proteins. An elastin-mimetic recombinant protein, TGPG[VGRGD(VGVPG)6]20WPC, referred to as [RGD-V6]20, contains multiple RGD motifs to bind cell-surface integrins. This study aimed to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Since increased surface density of this binding motif has been shown to enhance cell adhesion [43], the higher concentration of RGD peptide sequences on the RGD-ELP-coated substrate compared to the FN-coated substrate may result in enhanced cell adhesion on the RGD-ELP-coated substrate. However, this may not be able to fully explain different cell adhesion between RGD-ELPand FN-coated substrates because our previous study has also shown that cells have a higher affinity to the RGD motif of FN than to that of RGD-ELP [44]. Further studies are needed to investigate how the factors of concentration and affinity of RGD affect cell adhesion between RGD-ELP-and FN-coated substrates.…”
Section: Discussionmentioning
confidence: 89%
“…Since increased surface density of this binding motif has been shown to enhance cell adhesion [43], the higher concentration of RGD peptide sequences on the RGD-ELP-coated substrate compared to the FN-coated substrate may result in enhanced cell adhesion on the RGD-ELP-coated substrate. However, this may not be able to fully explain different cell adhesion between RGD-ELPand FN-coated substrates because our previous study has also shown that cells have a higher affinity to the RGD motif of FN than to that of RGD-ELP [44]. Further studies are needed to investigate how the factors of concentration and affinity of RGD affect cell adhesion between RGD-ELP-and FN-coated substrates.…”
Section: Discussionmentioning
confidence: 89%
“…The cRGDfC peptide appeared to have little effect on endodermal lineage specification. While it has been previously demonstrated that a number of neuronal cell types express αvβ3 integrins including radial glia cells [ 36 , 37 ], the role of RGD dependent integrins in ectodermal/neuronal differentiation has been suggested, but is less clear [ 38 ]. It is important to highlight, however, that the fold increases in gene expression of the tri-lineage markers were quite low and for the flow cytometry analysis the sub-population of positive cells were only identifiable in the Oct-4 negative population of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of MAP2 levels may be considered as a mere marker of reduced neuronal differentiation in ADAP knock-down cells. However, this phenomenon may also be more directly involved in the process as MAP2 is critical for dendritogenesis and dendritic outgrowth (Bernhard et al, 1985 ; Harada et al, 2002 ) and the level of MAP2 expression is controlled by integrin stimulation in developing neurons (Domingo-Espín et al, 2012 ; Jeon et al, 2012 ). Axonal growth was not significantly affected in our experiments, but might well be responsive to ADAP manipulation at an earlier time of differentiation.…”
Section: Discussionmentioning
confidence: 99%